Addressing schoolteacher food and nutrition-related health and wellbeing: a scoping review of the food and nutrition constructs used across current research - Tammie Jakstas; Berit Follong; Tamara Bucher; Andrew Miller; Vanessa A. Shrewsbury; Clare E. Collins (BMC, 2023)
Abstract Background Teachers form a large and essential workforce globally. Their wellbeing impacts personal health-related outcomes with flow on effects for the health, and wellbeing of their students. However, food and nutrition (FN) interventions that include teachers, typically neglect the impact of personal FN factors on a teachers' ability to achieve optimal nutrition-related health and wellbeing, and successfully fulfil their professional FN roles as health promoters, gate keepers, educators', and role models. The aim of this review was to scope FN constructs that have been studied internationally regarding teacher FN-related health and wellbeing. Methods Six databases were searched, and papers extracted in June/July 2021. Eligibility criteria guided by the population, concept, context mnemonic included studies published after 2000, in English language, with an aspect of personal FN-related health and wellbeing, among in-service (practising) and pre-service (training), primary, and secondary teachers. Screening studies for inclusion was completed by two independent researchers with data extraction piloted with the same reviewers and completed by lead author, along with complete descriptive and thematic analysis. Results Ten thousand six hundred seventy-seven unique articles were identified with 368 eligible for full text review and 105 included in final extraction and analysis. Sixty-nine descriptive studies were included, followed by 35 intervention studies, with the main data collection method used to assess both personal and professional FN constructs being questionnaires (n = 99 papers), with nutrition knowledge and dietary assessment among the most commonly assessed. Conclusion FN constructs are used within interventions and studies that include teachers, with diversity in constructs included and how these terms are defined. The evidence from this scoping review can be used to inform data collection and evaluation in future epidemiological and interventional research that addresses teacher FN-related health and wellbeing.